The dimensions of educational counseling in the university environment - FRUJINA, Ioana Georgiana (Acta et Commentationes, Sciences of Education, 2026)
In the contemporary university environment, educational counseling plays a strategic role in supporting learning and adaptation to academic and social demands. It represents a complex formative process aimed at students’ personal, academic, and professional development. Through counseling, students develop skills of self-regulation, decision-making, and professional integration. Its psychological and social dimensions contribute to emotional balance, harmonious relationships, and overcoming difficulties, while strengthening learning strategies, autonomy, and the shaping of professional goals, all essential for a successful academic and professional path.